Building rural wealth through a value chain approach. Issue 2 (14th March 2020) - Rahe, Mallory L.; Hause, Amy
ABSTRACT: Rural wealth creation is a salient approach to local economic development. This paper advances the implementation of this practice by documenting how targeted business investments within a value chain built multiple forms of wealth. We provide exploratory evidence of how consideration of value chain gaps, wealth-building opportunities, potential for expansion, and an emphasis on improved livelihoods can prioritize the allocation of resources to support businesses. We further show how modest investments into targeted businesses built multiple forms of wealth throughout a value chain. Our results provide examples of how to implement the rural wealth creation concepts and a refined understanding of how to target business assistance in ways that build multiple forms of community capital.